The Relationship between Self-Concept and Self-Confidence of Junior High School Students - Tyas, Celine Astutiningtyas; Setiawan, Agus; Widiharto, Chr. Argo (IKIP Siliwangi, 2025)
Some students have low self-confidence and have a negative self-concept. The study aimed to determine the relationship between self-concept and self-confidence of second-grade students at SMP Negeri 1 Salem. This research was conducted in 2024. This study uses a correlational method with a descriptive correlational design. The results showed a relationship between self-concept and students' self-confidence. The degree of relationship between the self-concept variable and the self-confidence variable is correlated with a strong category in a positive form. This study's conclusion reveals a positive and significant relationship between self-concept and self-confidence of second-grade students at SMP Negeri 1 Salem. The higher the self-concept variable, the higher the self-confidence variable. The study strengthens the theory, stating that self-concept plays an important role in shaping students' self-confidence. The results can be a reference in developing theories related to adolescent developmental psychology.